RECONSTRUÇÃO HISTÓRICA DO PRIMEIRO GRUPO ESCOLAR DOS CAMPOS GERAIS: VICENTE MACHADO (1904) - Schram, Aline Cristina (2014)
This research is a part of a project called “Historical Reconstruction of Educational Institutions of Campos Gerais from 1889 to 1950” coordinated by the HISTEDBR research group – Campos Gerais-PR aiming at the historical reconstruction of the first group of Republican schools in Campos Gerais. The research particularly aims at identifying the historical context around the development project for groups of schools in Brazil during the Republican years. We also seek to understand the origins of the development project for groups of schools in Paraná and analyze the city of Castro with Vicente Machado Group in the early republican years. Despite of having only one group as object of study, the research is not conducted in an isolated nature; the analysis of the relationships surrounding a single object leads to the understanding of the several dimensions involved. In this context, the method applied is the historical and dialectical materialism. The objective is to understand the contradictions of the dialectical movement present in material relationships using History as assumption. All the dimensions of the object of the study are in an interdependence relationship proposing the breakthrough of capitalist structure. This perspective indicates that the categories permeating the research were the State, society, education, social classes. This direction led to an analysis on the economic and social contexts of the state of Paraná and the city of Castro. Brazil was inserted in an Imperial and slavery scenario when the advent of liberal ideas brought the discourse of breaking with all sorts of slavery and prepare the country to receive capitalist development, resulting in several political and ideological conflicts. Thereby, the research ranges the period from 1889 to 1904, when republican ideas were being established in the country. This selection aims at capturing the actual movement in the early years of the Brazilian Republic and find how republican ideas were grounded in the development of groups of schools. The collection of data used official documents, photographs, maps, drawings, newspapers, minutes, laws, decrees, regulations and resolutions, analyses and reflection to encompass the object of study.